Amphibia, Centrolenidae, Centrolene antioquiense (Noble, 1920): New records and geographical distribution in Colombia (2010)
ABSTRACT: The current work provides three new localities for Centrolene antioquiense (Noble, 1920), a small centrolenid endemic to Colombia and known for just four sites. An updated diagnosis and life pictures of this species are also presented. Centrolene antioquiense apparently inhabits the canopy of montane forest and its natural habitat has been severely reduced due to deforestation.Pontifícia Universidade Católica do Rio Grande do Sul, Programa de Pós-Graduação em Zoologia, Faculdade de Biociências. Avenida Ipiranga6681. CEP 90619-900. Porto Alegre, RS, Brazil. Universidad de Antioquia, Grupo Herpetológico de Antioquia, Instituto de Biologia. Calle 67 # 53–108, Bloque 7–121, A.A. 1226. Medellín, Colombia.E-mail: mauricio.rivera@acad.pucrs.brMauricio Rivera-CorreaAmphibia, Centrolenidae, Centrolene antioquiense(Noble, 1920): New records and geographical distribution in Colombiatympanic annulus completely visible; (4) dorsal skin finely shagreened; (5) periclocal region with small tubercles enameled present, cloacal fold absent; (6) in preservative, anterior 1/3 parietal peritoneum covered by iridophores (not transparent), pericardium, gastric and intestinal peritonea covered by iridophores (enameled white), hepatic peritoneum transparent; (7) humeral spine in adult males present; (8) webbing absent between fingers I and II; webbing between outer fingers reduced, II 3+ – 4 1/4 III 3+ − 2 IV; (9) webbing formula on foot I 2 − 2 2/3 II 1 – 3+ III 2 – 3+ IV 3+ − 1 V; (10) outer ulnar fold enameled and outer tarsal fold absent but small tubercles enameled present; (11) nuptial excrescences type–I; (12) upper lip white, dorsolateral section of body with enameled warts extending from the lower edge of the eye to the groin; (13) in life, dorsum yellowish green with scattered yellow and white spots, bones green in life; (14) in preservative, lavender with scattered white spots and flecks; (15) iris white grayish with blue dots, gold spots and fine blue reticulations; (16) adult males SVL 20.5 – 22.5 mm (X = 21.5 mm, SD = 1.0, N = 22), SVL unknown in adult females.Recent research on glassfrogs has substantially increased our understanding of their evolution, systematics and taxonomy (see Cisneros-Heredia and McDiarmid 2007; Guayasamin and Trueb 2007; Guayasamin et al.2008; 2009). However there are still gaps in our basic knowledge of their geographical distribution, mainly in the Andean region of Colombia. The new records of Centrolene antioquiense presented herein are important geographic extensions, representing the northernmost and southernmost localities for the species (ca. 32 km NW from Yarumal, and ca. 60 km S of Libano).Centrolene antioquiense has been considered a rare species, and few vouchers have been deposited at scientific collections. The species seems to be difficult to find because it apparently inhabits the canopy of montane forest and its natural habitat has been severely reduced due to deforestation (Ruiz-Carranza and Lynch 1997)